Anatexis of accretionary wedge, Pacific‐type magmatism, and formation of vertically stratified continental crust in the Altai Orogenic Belt. Issue 12 (27th December 2016) - Jiang, Y. D.; Schulmann, K.; Sun, M.; Štípská, P.; Guy, A.; Janoušek, V.; Lexa, O.; Yuan, C.
Abstract: Granitoid magmatism and its role in differentiation and stabilization of the Paleozoic accretionary wedge in the Chinese Altai are evaluated in this study. Voluminous Silurian‐Devonian granitoids intruded a greywacke‐dominated Ordovician sedimentary succession (the Habahe Group) of the accretionary wedge. The close temporal and spatial relationship between the regional anatexis and the formation of granitoids, as well as their geochemical similarities including rather unevolved Nd isotopic signatures and the strong enrichment of large‐ion lithophile elements relative to many of the high field strength elements, may indicate that the granitoids are product of partial melting of the accretionary wedge rocks. Whole‐rock geochemistry and pseudosection modeling show that regional anatexis of fertile sediments could have produced a large amount of melts compositionally similar to the granitoids. Such process could have left a high‐density garnet‐ and/or garnet‐pyroxene granulite residue in the deep crust, which can be the major reason for the gravity high over the Chinese Altai. Our results show that melting and crustal differentiation can transform accretionary wedge sediments into vertically stratified and stable continental crust. This may be a key mechanism contributing to the peripheral continental growth worldwide. Key Points: Ordovician accretionary wedge sediments in the Chinese Altai may be a viable source for Pacific‐type Silurian‐Devonian granitoids Melting of accretionary wedge left behind granulitic residue that can explain gravity high over the Chinese Altai Melting and crustal differentiation of the accretionary wedge sediments can transform oceanic material into stabilized continent